2019
DOI: 10.1109/access.2019.2941316
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonally Precoded Massive MIMO for High Mobility Scenarios

Abstract: Massive multiple-input multiple-output (MIMO) systems are of high interest for ultrareliable low-latency communication (URLLC) links. They provide channel hardening, i.e. reduced channel variations, due to the large number of transmit antennas which exploit spatial diversity by beam-forming. Massive MIMO requires channel state information (CSI) on the base station side. For time-varying vehicular communication channels the CSI acquired during the uplink phase will be outdated for the following downlink phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…More recently, we have proposed a sparse WH waveform in [10], where we have shown that the equal-gain is achieved with sparse spreading, which can be implemented with lower complexity. In summary, our results in [4], [5], [10] and the analysis of [8], [9] are complementary approaches that lead to the same conclusion: data symbols should experience the same channel gain to maximize performance. In this paper, we denote this condition as equal gain criterion (EGC).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…More recently, we have proposed a sparse WH waveform in [10], where we have shown that the equal-gain is achieved with sparse spreading, which can be implemented with lower complexity. In summary, our results in [4], [5], [10] and the analysis of [8], [9] are complementary approaches that lead to the same conclusion: data symbols should experience the same channel gain to maximize performance. In this paper, we denote this condition as equal gain criterion (EGC).…”
Section: Introductionmentioning
confidence: 67%
“…where the matrixH(n ini , N UW ) ∈ C NUW×NUW is defined in (9) in the bottom of next page, and is a quasi-circulant 1 channel matrix due to CP insertion. The quantity n ini represents the initial channel sample and T = N UW in ( 9) is due to the UW length.…”
Section: Receiver Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Different from those contributions, our work is interested in the impact of aged CSIT on the massive-MIMO-enabled URSST. Unlike the work in [19], [20] which consider deterministic time-varying channel models for the aged CSIT, our investigation is mainly based on the first-order Markov model of the aged CSIT, which is more appropriate for wireless environments that are rich in scattering. It is perhaps worth noting that MIMO (or massive-MIMO) beamforming with aged CSIT has already received intensive investigation for throughput-oriented systems and for the average performance (e.g., [21]- [23]), while our work targets on the reliability for every single shot.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in [15], the authors have proposed a large-antenna array based low-complexity receiver for decoding the downlink OTFS signal transmitted from a single-antenna BS. However, the authors ignore inter-carrier interference (ICI) and intersymbol interference (ISI) as they assume ideal pulse shaping transmit and receiver waveforms which satisfy the biorthogonality condition (see equation (17) in [15]). Such ideal pulses however do not exist.…”
Section: Introductionmentioning
confidence: 99%